(untitled) (PANGEEA, 2025)
The purpose of this paper is to explore the indispensable role of GIS in the hydrological modelling of the watersheds. The analysis of precipitation patterns of the watersheds represents one of the first focus in order to perform a drainage analysis. By integrating spatial data and advanced modelling techniques, GIS can be considered an essential tool in understanding and predicting the hydrological processes that govern precipitation distribution within watersheds. The article outlines the use of two crucial methods to delineate the watersheds: Thiessen Polygon and Inverse Distance Weighting Interpolation (IDW), in analysing precipitation patterns within watersheds. The insights gained through these approaches significantly contribute to enhanced water resource management, flood prediction and mitigation, and environmental conservation strategies.